Emotional demonstration (EMO DEMO) to improve exclusive breastfeeding: literature review - Sembiring, Gaipyana; Damayani, Ayi Diah; Yunus, Endriyani Martina; Pinaremas, Annisa Sali (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2024)
Background: Suboptimal breastfeeding practices cause 823,000 deaths in children under 5 years of age and 20,000 deaths in women due to breast cancer in the world every year. The Government's program to increase coverage of exclusive breastfeeding is contained in the 10 Steps Towards Successful Breastfeeding (LMKM) which states that health workers are required to provide exclusive breastfeeding education to mothers from the antenatal period. An Emo Demo is a way to convey nutritional messages with a behavior change communication strategy that uses Behavior Centered Design (BCD).Objectives: This literature review aims to analyze the effect of exclusive breastfeeding education using the emotional demonstration method (EMO DEMO) on exclusive breastfeeding.Methods: This research method is a literature review using PRISMA analysis with the PUBMED, Science Direct, Proquest, Springer, and Google Scholar databases from 2019-2023. The inclusion criteria in this Literature Review are using a period from 2019-2023. the type of article is original research. The exclusion criteria in this literature review are research subjects other than pregnant women, mothers who have children under 2 years old, and health cadres.Results: Exclusive breastfeeding education using the emo demo method increases knowledge, attitudes, self-efficacy, and exclusive breastfeeding. Emotional demonstration training increases cadres' knowledge and skills in providing exclusive breastfeeding education.Conclusions: Exclusive breastfeeding education innovations with emotional demonstration methods will help the government accelerate optimal breastfeeding practices to improve maternal and child health in Indonesia. It is hoped that health workers can apply the emo demo method in providing exclusive breastfeeding education.